2019
DOI: 10.3389/fgene.2019.01140
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding Ribonucleic Acid SNHG18 Promotes Glioma Cell Motility via Disruption of α-Enolase Nucleocytoplasmic Transport

Abstract: Glioma is a common malignancy with poor prognosis. Recent evidence suggests that the pathogenesis and progression of glioma involve long noncoding RNAs (lncRNAs). Previously, we showed that glioma cell radioresistance was enhanced by lncRNA SNHG18 in vitro and in vivo. In the present study, we showed that SNHG18 promoted the invasion and migration of glioma cells. SNHG18 was demonstrated to regulate the progression of epithelial-mesenchymal transition and cytoskeleton remodeling, thereby affecting cell motilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 35 publications
2
28
1
Order By: Relevance
“…In contrast, OTX2-AS1 was significantly enriched in the floor-plate cluster together with TP53TG1 , implicated in carcinoma but not as yet associated with a neuronal phenotype [ 33 ] ( Figure 6 D–F and Supplementary Figure S3E ). This cluster of immature cells was also characterized by SNHG18 [ 34 ], known to play an oncogenic role in glioma, LINC0052 [ 35 ], which acts as a sponge for miR-608, and the annotated transcripts AC026124.1 , AL132780.2 , and AC026401.3 ( Figure 6 D–F and Supplementary Figure S3E ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, OTX2-AS1 was significantly enriched in the floor-plate cluster together with TP53TG1 , implicated in carcinoma but not as yet associated with a neuronal phenotype [ 33 ] ( Figure 6 D–F and Supplementary Figure S3E ). This cluster of immature cells was also characterized by SNHG18 [ 34 ], known to play an oncogenic role in glioma, LINC0052 [ 35 ], which acts as a sponge for miR-608, and the annotated transcripts AC026124.1 , AL132780.2 , and AC026401.3 ( Figure 6 D–F and Supplementary Figure S3E ).…”
Section: Resultsmentioning
confidence: 99%
“…Overexpressing CRNDE promotes EMT in oral epithelial cell carcinoma and osteosarcoma [39,40]. In glioma, high SNHG18 expression enhances radiation resistance, and triggers EMT by increasing ENO1 expression [41]. To the best of our knowledge, no studies have investigated the effects of these lncRNAs on PMT in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that decreased expression of lncRNA-H19 inhibited HSC activation and alleviated liver fibrosis in vivo and in vitro 18 . lncRNA SNHG18 acts as a tumour suppressor in hepatocellular carcinoma(HCC)and an independent diagnostic marker for liver cancer 19 ; it promots cell motility by regulating EMT progression and remodelling the cytoskeleton 20 . The clinical and diagnostic value of SNHG18 in patients with HCC was investigated for the first time, and it was found that SNHG18 was significantly down-regulated in HCC tissues compared to the corresponding noncancerous tissues 21 .…”
Section: Discussionmentioning
confidence: 99%